Initiatives to increase childhood vaccination coverage: an international comparison - Kroneman, Madelon; Fermin, Alfons; Rechel, Bernd; Allin, Sara; Anell, Anders; Behmane, Daiga; Bengough, Theresa; Blümel, Miriam; Bryndová, Lucie; Davidovics, Krisztina; Belvis, Antonio Giulio De; Charalambous, Chrystala; et al. (Health policy, 2025)
Background Childhood vaccination rates fluctuate over time and do not always meet the levels recommended by the WHO. Objective This study aims to provide an overview of measures countries have introduced to increase vaccination rates. Methods We developed a structured data collection template that was completed by country experts from Europe, Israel, the USA, and Canada. Experts were identified using the European Observatory on Health Systems and Policies' HSPM (Health Systems and Policy Monitor) network. We approached experts from 32 countries and received responses from 22 countries. In the template we asked for measures introduced between 2014 and 2019. The experts were asked to indicate the type of intervention, the target population, possible positive and negative effects, and evidence on effectiveness. The information was collected between September 2019 and January 2020. Results We identified four main types of interventions: restrictive measures for the unvaccinated, financial incentives, measures supporting the logistics of vaccination, and vaccination promotion campaigns. Restrictive measures often involved expanding existing mandatory vaccination policies or limiting access to pre-school activities for unvaccinated children. Financial incentives for healthcare providers showed some positive effects. Regarding logistical support, several countries used schools as alternative vaccination sites, though this presented organisational challenges. Many countries invested in improving knowledge among both healthcare professionals and parents to encourage vaccine uptake. Conclusions Most initiatives implemented in the countries covered focussed on communication and knowledge enhancement. However, there is limited evidence on the impact of these measures on vaccination coverage.
Keywords: podpora zdraví; Izrael; Humans; Europe; Israel; Health Policy; Spojené státy americké; Canada; Internationality; Immunization Programs; Vaccination Coverage; Evropa; očkovací programy; Kanada; United States; lidé; internacionalita; dítě; zdravotní politika; pokrytí očkováním; Child; Vaccination; Health Promotion; vakcinace